Bullous pemphigoid: Associating with the multifaceted phenomenon of koebner - Sudhir U. K. Nayak; Shukriti D Shenoi; S Smitha Prabhu; Raghavendra Rao (Journal of Dermatology and Dermatologic Surgery, 2022)
Koebner phenomenon (KP) or isomorphic phenomenon often helps in diagnosis of certain conditions and often reflects disease activity. Although commonly reported with psoriasis, vitiligo, and lichen planus, KP has been occasional reported with other conditions. Bullous pemphigoid has a rare association with this and we report a case with scratching being the inciting factor. A 50-year-old female with no comorbidities presented with itchy fluid-filled lesions all over the body for 15 days. Examination showed generalized distribution of bullae and vesicles with linear bulla on the forearms. Histopathology and immunofluorescence studies were conclusive of bullous pemphigoid. KP has been reported in general due to mechanical trauma, therapy, dermatoses, or reactions. KP in bullous pemphigoid is rarely reported and it is mentioned in the category IV of Boyd and Nelder classification. The linear nature of bulla in our patient was suggestive of scratching being the inciting factor for KP, which has not been reported to the best of our knowledge.